Evaluation of Shore A hardness of maxillofacial silicones: the effect of dark storage and nanoparticles - Pınar Çevi̇k (Istanbul University, 2018)
DOI: 10.26650/eor.2018.469Purpose Little has been reported how the addition of nanoparticles could affect the hardness of maxillofacial silicones. The purpose of this study was to evaluate the effects of different types of nanoparticle additives and dark storage for 2-years on the Shore A hardness of two types of maxillofacial silicone elastomers. Materials and Methods A-2000 and A-2006 Room Temperature Vulcanized (RTV) silicone elastomers were tested in this study. Silaned silica, fumed silica and titanium dioxide nanoparticles at concentrations of 10% by volume were used as fillers for the maxillofacial silicone elastomers. A total of 64 silicone specimens were fabricated, which includes 8 samples, 30 x 10 mm in size, from each silicone elastomers for each subgroup and also controls. After the initial Shore A hardness measurements, specimens were kept in dark conditions at room temperature for 2 years. The final measurements were then taken from the silicone specimens. All data were statistically analyzed. Results For both types of silicones, there was statistically significant differences among study groups (p<0.001). Fumed silica group showed the lowest hardness values in A-2000 after storage. However, no significant difference was observed between control and fumed silica groups. Control group showed the lowest hardness values in A-2006, while the highest hardness values were found in fumed silica group; there was no significant difference between silica and silane groups. Conclusion Shore A values of the specimens were within the acceptable range for the maxillofacial silicones after aging. Nanoparticle addition did not prevent hardening of the silicone elastomers with time.